Metavesolje, spletne skupnosti in (resnični) mestni prostor - Ulubaş Hamurc, Asli (Urbani izziv, 2022)
With the COVID-19 pandemic, technological advancements and investments accelerated to create an alternative to the real world that makes it possible for various activities and experiences to be handled online. Among these developments, the metaverse comes to the fore because it makes possible real and virtual experiences simultaneously, regardless of the time and space the user exists in, and it acts as a mediator and medium to bring these two environments together. This article discusses the possible impacts of advancements in the metaverse on (real) urban space considering the socio-spatial dialectic through theory synthesis and adaptation. An overall evaluation of the socio-spatial impacts of this is also included and opened up for discussion. Based on a literature review, it is expected that technological developments like the metaverse will introduce a new organization to physical and virtual socio-spatial relations, and new socio-technological groups will be created in them and by using them.
Keywords: COVID-19 pandemic; figitalno; mestni prostor; metaverse; metavesolje; online communities; pandemija covida-19; phygital; spletne skupnosti; urban space